Warunki kształtowania się współczesnej struktury agrarnej Chin - Wincewicz-Bosy, Marta (Conditione of Creating the Contemporary Structure of Agriculture in China, 2008)
The article is on China's agriculture structure and on changes during ages from the beginnings of the country. Agriculture is the most important area of international policy because of hunger and global consumption. Many people suffer of hunger - China is one of the biggest countries in the world that needs to find a solution to poverty. But poverty is not only China's problem, this is a global problem so we all need to find out its causes and co-operate with China's government in attempts to find sound solutions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 250-258